GAMBARAN PENGETAHUAN GIZI SEIMBANG, POLA MAKAN, RIWAYAT PENYAKIT, DAN SOSIAL EKONOMI KELUARGA ANAK STUNTINGDI SMP NEGERI 2 RANTAU SELATAN - Melisa Puspita Sari; Albiner Siagian; Zulhaida Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
Some of studies indicate that family sosio economic is the cause of stunting. The low income affect to capability of feeding and causing bad dietary habit. It had opportunities of stunting. This research aims to know description about knowledge of balance nutrition, the consumption pattern, history of diseases and family sosio economic in stunting students in SMP Negeri 2 Rantau Selatan. Types of study is an observational of cross sectional study design. This sample of research is all stunting students as many as 112 students and use total sampling method. Data for this study using 24 hours food recall method and food frequency question form. This research held in July up to October 2017 in SMP Negeri 2 Rantau Selatan. This results showed the knowledge of balance nutrition of stunting students in good chategory but the consumption pattern is lack according to the food quantity based on macro nutrient and micro nutrient. According to the type of food, stunting students consump rices as staple food; fishes and eggs as side dishes; spinaches, kales, cassava leaves as vegetables. In great measure, stunting students don’t have history of diseases, and their mothers in well education but don’t have occupation . It causing low family income so the nutrtional adequacy can’t be fulfilled. From the result of this research suggested to public health office that gives balance nutrtion counseling to society especially to low income family. Suggested to school to provide healthy canteen so the stunting students can improve their growth with good consumption of food. Keywords: Balance nutrition, consumption pattern, history of diseases, sosio economic statue, stunting, students in SMP Negeri 2 Rantau Selatan.